Can a pharyngeal bulb prosthesis eliminate hypernasal speech in individuals with hypodynamic velopharynx? - Rizatto,Ana Julia dos Passos (2022)
ABSTRACT Purpose: to investigate the effectiveness of a pharyngeal bulb prosthesis to eliminate hypernasality in patients with operated cleft palate presenting with diagnosis of hypodynamic velopharynx. Methods: twenty patients with cleft palate, ages 11-40 years, presenting hypodynamic velopharynx participated in the study. Patients had their speech audio recorded twice, with and without prosthesis, simultaneously with nasometry. Three speech-pathologists rated the presence and absence of hypernasality. Perceptual and nasometric data without and with prosthesis were compared, using the McNemar Test (p<0.05). Results: three (15%) patients presented hypernasality without prosthesis and normal resonance with prosthesis, 3 (15%), normal resonance without prosthesis and hypernasality with prosthesis, 9 (45%), hypernasality without and with prosthesis, and 5 (25%), normal resonance in both conditions. Nasometry (≤27% cut off): 1 (5%), presented scores >27% without prosthesis and <27% with prosthesis, 2 (10%), scores <27% without prosthesis and >27% with prosthesis, 17 (85%), scores >27% in both conditions, and 1(5%), scores <27% in both conditions. The comparisons between the results were not significant (p=1.000). Conclusion: the pharyngeal bulb prosthesis alone is insufficient to eliminate hypernasality of patients presented with hypodynamic velopharynx. To this purpose, the combination between the prosthesis and speech therapy is required.